Tuberculosis and COVID-19 - Migliori, Giovanni Battista (Henry Stewart Talks, 2021)
Similarities and differences between TB and COVID-19, Evidence of COVID-19 and TB co-infection, Impact of co-infection on mortality, Research priorities and global GTN study results, BCG vaccine protection & COVID-19, Impact of COVID-19 on health services